HUBUNGAN ANTARA KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR FISIKA SISWA SMA - Ramadan, Muhammad; Putri Wulandari, Refika Aulia; Hasanah, Nur; Zahra, An'Nisa Nur; Ikmawati, Ikmawati; Kurniawan, Kurniawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Mathematics and physics are two interrelated disciplines, particularly at the high school level, where mathematical ability serves as a critical foundation for understanding physics concepts. This study aims to examine the relationship between students"™ mathematical skills and their physics learning outcomes through a literature review. The method used was library research, focusing on articles published between 2015 and 2025, selected based on keywords, credibility, and relevance to the topic, and then analyzed using a thematic synthesis approach. The findings indicate that most studies report a significant positive relationship, ranging from moderate to strong, between mathematical competence and students"™ achievement in physics. Mathematics functions not only as a technical prerequisite but also as a cognitive tool that supports problem-solving and conceptual understanding. However, evidence also shows that strong mathematical ability does not always guarantee optimal performance in physics, as learning outcomes are also influenced by misconceptions, motivation, and instructional strategies.